Augmented reality in vocational training: A systematic review of research and applications. (April 2022) - Chiang, Feng-Kuang; Shang, Xiaojing; Qiao, Lu
Abstract: Augmented reality (AR) technology is widely used in various fields. However, there are few systematic reviews on the application of AR in vocational training. To fill this research gap, the current study reviewed the application of AR technology in the training of various industries over a 20 year period (2000–2021). Through cross-referencing and abstract reading, 80 relevant studies were selected for the final analysis from two perspectives: the improvement of vocational skills (including application area, target audience, training objectives, and effects) and AR training technology (including AR application, AR training system, and device). Furthermore, CiteSpaceV was employed to analyze the research hotspots and trends of AR vocational training. The results indicated that AR training is frequently applied in the industry, vocational education and medical fields. Among these industries, AR has been most frequently used in medical training, industrial maintenance, and assembly. Furthermore, AR glasses, simulators, the Unity3D game engine, 360° panorama, AR systems and apps are becoming widely used for training tasks. The benefits of these systems have been identified. We also explored the impact of AR on vocational training results. Based on 17 empirical studies, this study summarized the results and advantages of AR vocational training. This verified that AR has a high promotion effect on vocational training when the meta-analysis method is used. Future researchers can study how vocational skills education can be combined with these new intelligent technologies to design more mature teaching practice cases. Highlights: Augmented reality in vocational training. A systematic review on the application of AR in vocational training. AR has a high promotion effect on vocational training.